2005
DOI: 10.1038/sj.bjp.0706128
|View full text |Cite
|
Sign up to set email alerts
|

Antisecretory actions of a novel vasoactive intestinal polypeptide (VIP) antagonist in human and rat small intestine

Abstract: 1 Vasoactive intestinal peptide (VIP) has been demonstrated in intestinal mucosal neurones and elicits chloride secretion from enterocytes. These findings have led to the proposal that VIP is a secretomotor neurotransmitter. Confirmation of such a role may now be possible with the development of PG 97-269, a high-affinity, selective antagonist of VIP type 1 (VPAC1) receptor, which is expressed by gut epithelial cells. We have evaluated the VIP antagonism and antisecretory potential of this novel compound using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 35 publications
2
46
0
1
Order By: Relevance
“…These results are similar to observations in the guinea-pig (Furness et al 2003) and suggest that the VIP/NPY/calretinin/TH neurons are secretomotor neurons. This accords with retrograde tracing studies that have shown that NPY-immunoreactive submucosal neurons project to the mucosa of the mouse small intestine (Van Nassauw et al 2000) and is consistent with VIP being a primary transmitter of secretomotor neurons, as has been demonstrated in other species, including human, rat, guinea-pig and cat Lundgren 2002;Banks et al 2005;Furness 2006). VIP is also a stimulant of secretion in the mouse small intestine (Cox et al 2001), although its role as a secretomotor neurotransmitter has not been directly investigated.…”
Section: Discussionsupporting
confidence: 88%
“…These results are similar to observations in the guinea-pig (Furness et al 2003) and suggest that the VIP/NPY/calretinin/TH neurons are secretomotor neurons. This accords with retrograde tracing studies that have shown that NPY-immunoreactive submucosal neurons project to the mucosa of the mouse small intestine (Van Nassauw et al 2000) and is consistent with VIP being a primary transmitter of secretomotor neurons, as has been demonstrated in other species, including human, rat, guinea-pig and cat Lundgren 2002;Banks et al 2005;Furness 2006). VIP is also a stimulant of secretion in the mouse small intestine (Cox et al 2001), although its role as a secretomotor neurotransmitter has not been directly investigated.…”
Section: Discussionsupporting
confidence: 88%
“…VIP both causes fluid secretion and increases blood flow [96,97], and there is evidence that collaterals from the VIP containing secretomotor neurons innervate arterioles in the submucosa [98]. In human, overproduction of VIP causes the watery diarrhea syndrome [99].…”
Section: Secretomotor and Secretomotor/vasodilator Neurons Controllinmentioning
confidence: 99%
“…The importance of VIP in CT-induced fl uid secretion is well supported by drug inhibition studies [35,90] . VIP antagonists are effective when given both before and following establishment of the secretory state and able to inhibit LT and ST secretion in addition to their effects on CT [35,90] .…”
Section: Vip Antagonistsmentioning
confidence: 87%
“…However, the 5-HT 3 receptor antagonist, granisetron, reversed fl uid and chloride ion secretion to net absorption [89] . However, LT and ST do not release 5-HT from enterochromaffi n cells in the small intestine and that the secretory state induced by these toxins is not inhibitable by 5-HT receptor antagonists [90] .…”
Section: -Ht Antagonistsmentioning
confidence: 89%
See 1 more Smart Citation